2020
DOI: 10.1101/2020.03.25.006643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute social isolation evokes midbrain craving responses similar to hunger

Abstract: When people are forced to be isolated from one another, do they crave social interactions in the same way a hungry person craves food? To address this question, we used functional magnetic resonance imaging (fMRI) to measure neural responses in participants (n=40) evoked by food and social cues after ten hours of mandated fasting or total social isolation. After isolation, people felt lonely and craved social interaction. Midbrain regions showed increased activation to food cues after fasting and to social cue… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 137 publications
(223 reference statements)
10
101
2
Order By: Relevance
“…Hence, loneliness should motivate to prosocial behaviors that help build meaningful social ties and fulfill one’s need to belong 14 16 . In line with this, previous work has shown that individuals who experience momentary feelings of loneliness crave for social interaction 17 . However, there is also evidence that lonely individuals are more negatively biased toward others and more socially withdrawn 18 , 19 .…”
Section: Introductionsupporting
confidence: 63%
“…Hence, loneliness should motivate to prosocial behaviors that help build meaningful social ties and fulfill one’s need to belong 14 16 . In line with this, previous work has shown that individuals who experience momentary feelings of loneliness crave for social interaction 17 . However, there is also evidence that lonely individuals are more negatively biased toward others and more socially withdrawn 18 , 19 .…”
Section: Introductionsupporting
confidence: 63%
“…They have to withdraw at home, whereas in normal times, excessive social withdrawal is considered as a psychiatric symptom (Tajan 2015;Lamblin et al, 2017). Interestingly, acute isolation may cause social craving, with neural craving responses similar to hunger, even at the neurofunctional level (Tomova et al, 2020). While regressive behavior and externalized symptoms can be observed in children in times of crisis, the manifestations of psychological suffering in this context may be more discreet in adolescents: sleep disturbances, problems with peers, isolation, and depression (Douglas et al, 2009).…”
Section: Lockdownmentioning
confidence: 99%
“…Loneliness is a predictor for the development of depression [9], and it is associated with worse prognosis for depressed individuals [10]. Recent research has found that social isolation triggers neural craving responses similar to hunger [11]. Therefore, people with preexisting loneliness may feel even more socially deprived during the pandemic, and this may negatively impact their mental health.…”
Section: Social Isolation and Lonelinessmentioning
confidence: 99%